Effect of E-Word of Mouth through Instagrams on Purchasing Decisions in Twin House Coffee & Kitchen Restaurant, Cipete, Jakarta Selatan - Sari, Dhiny Irena; Lemy, Diena Mutiara; Ingkadijaya, Rahmat (Jurnal Penelitian Pariwisata, 2018)
Social media is widely used for restaurant entrepreneurs to market their business due to its ease and low cost. One of such media is Instagram. This research is to determine the effect of Electronic Word of Mouth through Instagram in terms of Intensity dimensions, Valence of Opinion and Content and to find out whether E-Word of Mouth through Instagram has a joint influence on Purchasing Decisions at Twin House Coffee & Kitchen Restaurant, Cipete, South Jakarta. Quantitative research with a descriptive approach is employed. The population covers the customers of the restaurant for 6 months, as many as 20,255. Slovin formula is used to determine the sample size of 100 respondents. Non-probability sampling technique is carried out by convenience sampling technique. The results indicate that partially electronic word of mouth, namely the intensity dimension has a positive and significant influence on purchasing decisions, the valence variable of opinion does not have a positive and significant effect on purchasing decision variables. Content variables have a positive effect on purchasing decision variables. Simultaneously Intensity (X1), Valence Opinion (X2), and Content (X3) variables have a significant effect jointly on the purchasing decision variable (Y) at Twin house Coffee & Kitchen, Cipete Restaurant in South Jakarta.